Expansion dynamics and emission characteristics of nanosecond–picosecond collinear double pulse laser-induced Al plasma in air. (February 2020) - Cao, Shiquan; Su, Maogen; Ma, Pengpeng; Wang, Kaiping; Min, Qi; Sun, Duixiong; Cheng, Rui; Ying, Yangjun; Dong, Chenzhong
Highlights: A systematic diagnosis study is performed to understand the expansion dynamics and emission characteristics of collinear double pulse (DP) laser-induced Al plasma in air at atmospheric pressure by combining shadowgraphy, interferometry, and spectrometry. Some distinctive evolution properties of the shock waves are observed, including the colliding and merging of picosecond and nanosecond shock waves, but more particularly the appearance of a third shock wave and the formation of an interaction layer. The plume expansion and electron density distribution of collinear DP laser-induced Al plasma are discussed by comparison with single pulse (SP) case based on the diagnosis results of interferometry and spectrometry. A signal enhancement for atomic and ionic lines is observed and analyzed in the collinear DP case. Abstract: A systematic diagnosis study was performed to understand the expansion dynamics and emission characteristics of nanosecond–picosecond collinear double pulse laser-induced plasma (DP-LIP) of aluminum in air at atmospheric pressure by combining shadowgraphy, interferometry, and spectrometry. The expansions of the shock waves were investigated using shadowgraphic images, and their distinctive evolution properties were analyzed, including the colliding and merging of picosecond and nanosecond shock waves, but more particularly the appearance of a third shock wave and the formation of an interaction layer. The plume expansion and electron density distribution of DP plasma were discussed by comparison with single pulse (SP) plasma based on the diagnosis results of interferometry and spectrometry. In addition, evolution characteristics of emission spectra of different species in SP and DP cases were also analyzed and evident signal enhancements for atomic and ionic lines were obtained in collinear DP case.